The Effect of Flipped Classroom toward Students’ Achievement in Teaching Reading - Kurniawan, Erwin Hari; Wulandari, Sri (JET ADI BUANA, 2018)
Flipped Classroom is a teaching strategy that combines technology in traditional teaching which today is commonly called blended learning. The flipped classroom is an opposite of traditional instructional procedures and usually done in the classroom in traditional learning to be performed at home in the flipped classroom, and usually carried out at home as homework in traditional learning to be implemented in the classroom in the flipped classroom. This research is aimed to knowhow students reading achievement can be improved by the effect of flipped classroom. To design this research, Action Research was chosen. There are two cycles on this research. Each cycle covered four steps; those were planning, implementing, observing and reflecting. The subject of this study was students in critical reading class consisting of 32 students. To gain the data, test, observation sheet, and interview were used. From the result analysis showed that the students reading achievement was improved by using flipped classroom. So, it was concluded that during the teaching and learning process students were more active and enthusiastic. They had good willingness in following reading class. In the last, it was recommended to use Flipped Classroom as the alternative strategy to teach reading.